Bonding in Barium Boryloxides, Siloxides, Phenoxides and Silazides: A Comparison with the Lighter Alkaline Earths. Issue 46 (7th July 2021) - Le Coz, Erwann; Hammoud, Joanna; Roisnel, Thierry; Cordier, Marie; Dorcet, Vincent; Kahlal, Samia; Carpentier, Jean‐François; Saillard, Jean‐Yves; Sarazin, Yann
Abstract: Barium complexes ligated by bulky boryloxides [OBR2 ] − (where R=CH(SiMe3 )2, 2, 4, 6‐ i Pr3 ‐C6 H2 or 2, 4, 6‐(CF3 )3 ‐C6 H2 ), siloxide [OSi(SiMe3 )3 ] −, and/or phenoxide [O‐2, 6‐Ph2 ‐C6 H3 ] −, have been prepared. A diversity of coordination patterns is observed in the solid state for both homoleptic and heteroleptic complexes, with coordination numbers ranging between 2 and 4. The identity of the bridging ligand in heteroleptic dimers [Ba(μ2 ‐X1 )(X2 )]2 depends largely on the given pair of ligands X1 and X2 . Experimentally, the propensity to fill the bridging position increases according to [OB{CH(SiMe3 )2 }2 )] − <[N(SiMe3 )2 ] − <[OSi(SiMe3 )3 ] − <[O(2, 6‐Ph2 ‐C6 H3 )] − <[OB(2, 4, 6‐ i Pr3 ‐C6 H2 )2 ] − . This trend is the overall expression of 3 properties: steric constraints, electronic density and σ‐ and π‐donating capability of the negatively charged atom, and ability to generate Ba ⋅ ⋅ ⋅ F, Ba ⋅ ⋅ ⋅ C(π) or Ba ⋅ ⋅ ⋅ H−C secondary interactions. The comparison of the structural motifs in the complexes [Ae{μ2 ‐N(SiMe3 )2 }(OB{CH(SiMe3 )2 }2 )]2 (Ae = Mg, Ca, Sr and Ba) suggest that these observations may be extended to all alkaline earths. DFT calculations highlight the largely prevailing ionic character of ligand‐Ae bonding in all compounds. The ionic character of the Ae‐ligand bond encourages bridging coordination, whereas the number of bridging ligands is controlled by steric factors. DFT computations also indicate that in [Ba(μ2 ‐X1 )(X2 )]2 heteroleptic dimers, ligand predilection for bridging vs. terminal positions is dictated by the ability to establish secondary interactions between the metals and the ligands. Abstract : Barium and related alkaline‐earth complexes bearing combinations of boryloxides, siloxides, phenoxides and amides have been structurally authenticated. Their structural patterns and bonding properties have been thoroughly investigated by DFT calculations.